RoCL: a resource oriented communication library - Alves, Albano (2009)
RoCL is a communication library that aims to exploit the low-level communication facilities of today’s cluster networking hardware and to merge, via the resource oriented paradigm, those facilities and the high-level degree of parallelism achieved on SMP systems through multi-threading. The communication model defines three major entities – contexts, resources and buffers – which permit the design of high-level solutions. A low-level distributed directory is used to support resource registering and discovering. The usefulness and applicability of RoCL is briefly addressed through a basic modelling example – the implementation of TPVM over RoCL. Performance results for Myrinet and Gigabit Ethernet, currently supported in RoCL through GM and MVIA, respectively, are also presented.